Valence electron concentration-dependent stability of L12, D023, and D022 ordered phases in high-entropy alloys - Mizuseki, Hiroshi; Sahara, Ryoji; Hongo, Kenta (Elsevier BV, 2025)
We investigate the valence electron concentration (VEC) dependence of semi-ordered phases (SOPs) in highentropy alloys (HEAs) via first-principles calculations. Fifteen equiatomic quaternary alloys composed of Al, Fe, Co, Ni, Cu, and Zn, along with non-equiatomic CrFeCoNi alloys, are analyzed. Formation energies of L12, D022, D023, and random solid solution (RSS) phases are evaluated. The results reveal that SOPs consistently exhibit lower formation energies than RSS. Although D023 phases have not yet been experimentally observed in HEAs, they are predicted to stabilize in specific intermediate VEC regions depending on composition, bridging the stability regimes of L12 and D022. These findings clarify VEC-dependent stability trends and provide insights into conditions favoring D023 formation in HEAs.